2006
DOI: 10.1002/pmic.200500023
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a 2-D human urinary proteomic map in IgA nephropathy

Abstract: Immunoglobulin A nephropathy (IgAN) is the most common form of immune complex-mediated glomerulonephritis worldwide. Although chronic renal failure develops in considerable numbers of IgAN patients, the exact etiology has not yet been clearly elucidated. To establish the urinary protein map of IgAN, we performed a urinary proteomic analysis. Thirteen patients with IgAN and 12 normal controls were recruited. Morning midstream spot urine samples were used with Centriprep ultrafiltration for concentration and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 27 publications
2
42
0
1
Order By: Relevance
“…␣1-Antitrypsin was identified as a potentially upregulated biomarker; this finding was confirmed by Western blotting. More recently, Park et al (73) examined pooled urine from 13 patients with IgA nephropathy and compared the data with those from 12 normal control subjects. The authors found an array of differentially present proteins and used the data to initiate the establishment of a human urinary proteome map of IgA nephropathy.…”
Section: Identification Of "Biomarkers" For Kidney Diseasesmentioning
confidence: 99%
“…␣1-Antitrypsin was identified as a potentially upregulated biomarker; this finding was confirmed by Western blotting. More recently, Park et al (73) examined pooled urine from 13 patients with IgA nephropathy and compared the data with those from 12 normal control subjects. The authors found an array of differentially present proteins and used the data to initiate the establishment of a human urinary proteome map of IgA nephropathy.…”
Section: Identification Of "Biomarkers" For Kidney Diseasesmentioning
confidence: 99%
“…32 Most studies have looked at the soluble urine protein fraction, focusing on the identification of potential biomarkers in renal disease and diseases of the urogenital tract. They include studies of acute kidney injury, 33,34 acute renal allograft rejection, 35-38 glomerular disease [39][40][41][42][43][44][45][46] and carcinoma of the kidney, bladder and prostate. [47][48][49] In many cases the reported biomarkers remain unidentified, although some studies have proceeded to identification of the biomarker proteins.…”
Section: Current Biomarker Candidatesmentioning
confidence: 99%
“…In proteomic analysis of urine from patients with IgA nephropathy, the authors found an array of differentially present proteins and used the data to initiate the establishment of a human urinary proteome map of IgA nephropathy. [40] In a recent study of focal segmental glomerulosclerosis (FSGS), 37 urinary proteins were identified, showing characteristic patterns of dynamic changes along the disease course of FSGS. [41] Some urinary proteins appearing earlier than glomerular sclerosis could serve as potential early diagnostic biomarkers.…”
Section: Protein Expression Profiles In the Normal Urinementioning
confidence: 99%